ANALISIS HUBUNGAN ANTARA ARUS KAS DARI AKTIVITAS OPERASI DAN DATA AKRUAL DENGAN RETURN SAHAM STUDI EMPIRIS PADA BURSA EFEK JAKARTA - HERIBERTUS KURNIAWAN; NUR INDRIANTORO (Jurnal Bisnis dan Akuntansi, 2000)
This study examines whether operating cash flow and accrual have relationship with stock return. Previous studies show that earnings have information content. Some studies of earnings component show that the results are not consistent. This research uses sample of 55 manufacturing firms listed in Jakarta Stock Exchange selected using purposive sampling method. The criteria for the purposive sampling nethod are that manufacturing firms have go public before December 31, 1995, these firms have reported cash flow statements for 1995 and 1996, and their common stock traded actively.This research tests of five hypothesis use multiple regression. The assumption for the multiple regression is alsa tested. Result of the assumption test, autocorellation, multicollinearity, and heteroscedasticity are statisfied. The result of the examinatopn show that mulls hypothesis cannot be rejected by using earning component deflator.